Dosimetry: which dose for screening, diagnosis and follow-up ? - D Tack; H Salame (Journal of the Belgian Society of Radiology, 2013)
The question of which dose for screening, diagnosing ad follow-up of pulmonary nodules is a permanent issue for radiologists and radiotherapists. The proposed dose values for 2013 reflect the possibilities of the latest CT generations, from 2010 or later and include all technical novelties such as iterative reconstructions, automatic tube potential selection, and latest detectors. As the technology is constantly evolving, these parameters are susceptible to lower every year.